Processo de autoavaliação do Programa de Pós-Graduação em Biociências e Saúde: construindo ferramentas - Berté, Italoema Agnelo Alves (2021)
Evaluating the educational processes is the appropriate strategy to understand how the proposed training process is progressing. Faced with the new demands for evaluation by the Coordination for the Improvement of Higher Education Personnel (Capes) the need arises for the systematic evaluation of graduate programs to emerge beyond the quantitative aspects of scientific production. Among the new Capes guidelines, the self-assessment is being highlighted. Defined as internal evaluation or institutional evaluation, it must involve all the stakeholders in the formulation of evaluation and in actions to be evaluated. The general objective of this research is to build and validate tools to mediate the self-evaluation process in the Graduate Program in Bioscience and Health. It is a methodological study, of a quantitative nature, developed in two stages. The first stage embodies the construction of instruments to support the self-evaluation of the Graduate Program, aimed at professors, university staff members involved in the activities of the program; masters and PhD students and alumni. For the construction of the instruments, the self-evaluation system of the Graduate Program proposed by Capes was considered and for the organization of the data, the theoretical-methodological model proposed by Donabedian was chosen, in which the evaluation considers the structure of domains, process and result. In the second stage, the content validation of the instruments produced was carried out, in order to identify the suitability of the instruments. The study participants were selected following the logic of non-probabilistic intentional sampling, in which the participants, being considered knowledgeable about the subjects studied, were appointed in the study as expert judges. These were distributed by categories, according to the specificity of each instrument to be validated. For this, there are four categories of expert judges: professors, university staff members, masters and PhD students, and alumni. The data collection technique was the online survey through Google Forms tool, in which the links of the instruments were triggered to the participants through their electronic addresses, obtained on the websites and pages of the graduate programs. In total, 63 expert judges participated: 29 professors, 8 university staff members, 13 master's and PhD students and 13 alumni. From the responses of the evaluators to the validation process, the adequacy was observed in relation to the total number of questions. The responses in relation to the domains indicated that the most appropriate was Structure (91%), followed by very close values for the domain Profile (86.5%), Results (86%) and Process (85.75%). Among the judges, the group of professors answered more positively, indicating that 93±5,3% of the questions were adequate. After them, the alumni group with answers that represented 90±7,0% of adequality.